Jazzowe infiltracje w literaturze czeskiej w latach 20. XX wieku - Novak, Radomil (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2012)
The article is concentrated on jazz inspiration in the Czech culture of the 1920s, especially its infiltration to the Czech poetry. Contemporary manifests, anthologies, essays and critics has been researched so as to detect the influence of this new musical phenomenon over the Czech avant-garde art. The inspiration by jazz music then have been discovered in concrete books of poetry by E. F. Burian, V. Nezval, J. Seifert, J. Voskovec and J. Werich. The jazz motives as ‘jazz-band, black, saxophone etc.’ as well as imitation of a blues form were found there. In conclusion, the author points to the fact that the jazz music has become the symbol of the new revolutionary art, identified with the left-wing avant-garde, and it has brought a new view of reality, methods and functions of art.